Educational Media Introduction To Human Internal And External Organs For High School Students Based On Augmented Reality By Using The Assemblr Application - I Dewa Ayu Sri Murdhani; Yunika Putri Oktavia; Muhammad Sholeh (International Journal of Applied Sciences and Smart Technologies, 2023)
The development of information technology from year to year always experiences very rapid development, and one of the positive impacts of this development is the existence of innovation in the field of education. Education today already uses information technology, especially augmented reality (AR). The purpose of this study is to help high school students in getting to know human internal and external organs through 2D or 3D virtual objects projected against the real world. The features in the educational media for the introduction of human internal and external organs are learning materials, quizzes, and games to hone students' knowledge. The research method used is research and development (RD). This research will produce AR applications that discuss human internal and external organs, in addition to the features that will be produced, namely learning materials, quizzes, and games. With these 3 features, it is hoped that high school students will understand the material about human internal and external organs. AR-based learning media is developed using the Assemblr application. Keywords: Augmented Reality, Internal Organs, External Organs, Assemblr